2020
DOI: 10.3390/antibiotics9070401
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Renal Function and Age on the Pharmacokinetics of Levofloxacin in Patients with Bone and Joint Infections

Abstract: Despite its efficacy and toxicity being exposure-related, levofloxacin pharmacokinetics in patients with bone and joint infections has been poorly described to date, so the possible need for a dose adjustment is unknown in this population. A prospective population pharmacokinetic study was conducted in 59 patients to answer this question. The final model consisted of a one-compartment model with first-order absorption and elimination. Mean parameter estimates (% interindividual variability) were 0.895 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…19 full papers were reviewed, different reports of the same clinical study and literature inconsistent with the content of this study were excluded, and references of relevant literature were searched to prevent literature omission. Finally, a total of 12 RCTs were included in the study [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. All the retrieval and screening processes were completed by two evaluators independently, and any different opinions were unified through internal discussion (Table 1).…”
Section: Literature Retrieval Results and Included Researchmentioning
confidence: 99%
“…19 full papers were reviewed, different reports of the same clinical study and literature inconsistent with the content of this study were excluded, and references of relevant literature were searched to prevent literature omission. Finally, a total of 12 RCTs were included in the study [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. All the retrieval and screening processes were completed by two evaluators independently, and any different opinions were unified through internal discussion (Table 1).…”
Section: Literature Retrieval Results and Included Researchmentioning
confidence: 99%
“…In hospitalized elderly patients with varying degrees of renal function, CL CR was again shown to be the main covariate associated with interindividual variability in LEV CL [90]. A prospective population PK study conducted in patients with bone and joint infections demonstrated that age and glomerular filtration rate were covariates related to interindividual variability of CL/F [81]. Critical illness was not a significant variable in altering LEV CL per se, with altered renal function being the determining factor [77,[93][94][95][96].…”
Section: Elimination Process: Role Of Renal and Hepatic Functionmentioning
confidence: 97%
“…Approximately 83% of LEV is excreted in the urine as an unchanged drug, indicating that it primarily undergoes renal elimination [36,39]. Similarly to CIP, population PK modeling has been used in several studies with LEV to estimate the effect of individual PK parameter values in a variety of patient populations and bacterial infections [70,[81][82][83][84][85][86][87][88][89][90][91][92][93] (Table 2). In several studies, CL CR [71,[82][83][84][85][91][92][93], age [70], and race [70] were found to be covariates that influenced the CL of LEV.…”
Section: Elimination Process: Role Of Renal and Hepatic Functionmentioning
confidence: 99%
“…19 A patient of periprosthetic knee infection caused by Streptococcus anginosus, was successfully treated by vancomycin (1 g, q12h, iv) and levofloxacin (750 mg, qd, iv) for 4 weeks, and then levofloxacin (750 mg, qd, po) for 2 weeks. 54 In 2020, Eloy et al 55 developed a PPK model of levofloxacin with 59 OAI patients, and the model consisted of a one-compartment model with first-order absorption and elimination. Monte Carlo simulations evaluated the PTA of levofloxacin at a dose of 750 mg, qd, with different ages and renal functions.…”
Section: Fluoroquinolonementioning
confidence: 99%